Speaking of freedom? Heritage, memory and public remembering in Kliptown - Roux, Naomi (My University, 2009)
Abstract In 2005, the Johannesburg Development Agency (JDA) officially unveiled a new heritage precinct in Kliptown, Johannesburg, marking the site where the 1955 Congress of the People took place. This heritage development, centred around the Walter Sisulu Square of Dedication (WSSD), has been contentious since its inception. Many Kliptown residents have expressed the feeling that pressing issues of housing and service delivery have been overlooked by the state in the process of developing WSSD and surrounds. Additionally, many residents do not feel that the new precinct is accessible, either physically or psychologically. One possible reason for this is that the heritage presented by the JDA at this site excludes large portions of Kliptown’s heritage which are locally important, and which played a significant role in the decision to host the Congress of the People in Kliptown. This report uses interview data and oral histories to uncover some of these silenced narratives of Kliptown’s history and heritage, and to examine the significance of these narratives for those living in Kliptown. Analysing these local narratives, it is apparent that Kliptown’s heritage as experienced and understood by residents is much more complex and contested than the simple linear narrative on display in WSSD. The JDA heritage developments focus largely on tangible means of representing the story of the Congress of the People and the Freedom Charter. However, Kliptown residents’ narratives about the area’s past are, to a large extent, based on aspects of Kliptown’s heritage which are intangible, such as traditions of independence and resistance. Much of this heritage has been preserved by means of oral history. I argue that this subtle understanding of heritage is more in keeping with the stipulations of the Heritage Resources Act (1999) than the approach taken by the JDA to commemoration in Kliptown, and suggest that these local memories and means of commemoration urgently need to be taken into account if future heritage projects in Kliptown are to be successful.